1959
DOI: 10.2307/1539156
|View full text |Cite
|
Sign up to set email alerts
|

The Physiology of Skeleton Formation in Corals. I. A Method for Measuring the Rate of Calcium Deposition by Corals Under Different Conditions

Abstract: The purpose of this study is to examine the rate of growth of reef-building corals by measuring the calcium deposition in the skeleton with the aid of a new method using radioactive calcium-45 as tracer. With this procedure it was possible to determine calcification rates in the different parts of coral colonies, and to estimate quantitatively the effect of light and darkness, zooxanthellae and carbonic anhydrase inhibitors on skeletogenesis.Numerous attempts have been made in the past to estimate the growth r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
213
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 439 publications
(236 citation statements)
references
References 14 publications
15
213
0
Order By: Relevance
“…Conversely, the concept of light-enhanced calcification has been well established (Kawaguti and Sakumoto 1948;Gordeau 1959;Goreau and Goreau 1959) and can increase coral calcification rates by three to ten times compared with rates in the dark Moya et al 2006). Light availability may also determine the susceptibility of reef building corals to pressures from OA.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the concept of light-enhanced calcification has been well established (Kawaguti and Sakumoto 1948;Gordeau 1959;Goreau and Goreau 1959) and can increase coral calcification rates by three to ten times compared with rates in the dark Moya et al 2006). Light availability may also determine the susceptibility of reef building corals to pressures from OA.…”
Section: Introductionmentioning
confidence: 99%
“…shown that coral living in shallow waters has a higher growth rate than those living in deep water (e.g., Goreau, 1959;Marubini et al, 2001;Sun et al, 2008). So the limited growth rate change here is in favor of a limited living-depth change.…”
Section: Origin Of the Intra-skeletal Calcite: Biogenic Vs Early Diamentioning
confidence: 79%
“…In contrast, during light no negative impacts of OA on calcification could be observed. Photosynthesis may thus offset impacts of OA by buffering pH during light, increase X ar and, therefore, facilitate deposition of CaCO 3 (Al-Horani et al 2003;Borowitzka and Larkum 1976b;Goreau 1959;N. Vogel et al pers.…”
Section: Discussionmentioning
confidence: 99%